Live@WPU UiTMCT "literature search: hunting through EzAccess" & eExhibition@Library Vol. 1/2021: tanaman lanskap - pokok renek / Asmahani Abdullah - Abdullah, Asmahani (Perpustakaan Tun Abdul Razak, 2021)
IQRA': Bil.1/2021 Januari